A lesson from COVID-19 pandemic: Developing a survival investment strategy to deal with crisis conditions - Rinaldo, Dito; Vina Anggilia Puspita; binti Fatahul Ariffin, Hazelena Dewi (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2022)
This study introduces the novel concept of a stock investment strategy tailored to crises. It adopts a quantitative approach that tests various factors influencing stock price dynamics. In the first stage of the study, a multiple regression analysis is conducted, encompassing macroeconomic indicators such as Southeast Asian, Chinese, and American stock indexes, gold prices, and the impact of COVID-19 on stock prices. Subsequently, an additional examination assesses the influence of LQ-45 company performance on stock price formulation. Finally, a qualitative analysis is employed to scrutinize government policies implemented during the pandemic and their impact on Jakarta Composite Index (JCI) movements. As a result, it is found that all macroeconomic factors exert a significant negative influence on stock prices. Additionally, as COVID-19 cases surge, stock indexes in Southeast Asia, China, and America exhibit a substantial positive effect on stock prices. In contrast, firm performance and gold prices do not significantly affect stock price movements. Moreover, the market also reveals a more favorable response to government initiatives aimed at relaxing activity restrictions and positive developments in vaccination efforts. Lastly, based on the extensive analyses conducted in this study, we have identified four distinct investment strategies tailored explicitly for effectively navigating crises. These strategies encompass diversification, a prudent wait-and-see approach, the Richman party, and the Guerrilla strategy.